Assessing fishery management models in the Kampar River, Riau Province, Indonesia, using Ecosystem Approach to Fisheries Management (EAFM) tool - EKO PRIANTO; ROMIE JHONNERIE; YOSSI OKTORINI; ADRIMAN ADRIMAN; NUR EL FAJRI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Prianto E, Jhonnerie R, Oktorini Y, Adriman, Fajri NE. 2024. Assessing fishery management models in the Kampar River, Riau Province, Indonesia, using Ecosystem Approach to Fisheries Management (EAFM) tool. Biodiversitas 25: 4581-4592. The Kampar River's high fish diversity dramatically benefits the local community. However, overfishing threatens the river's fishery resources. Urgent and concerted management efforts, including local wisdom implementation, are crucial to address this pressing issue. Law Number 45 of 2009 concerning fisheries mandates sustainable fishery resource management, primarily through an ecosystem-based approach. From January to June 2024, researchers conducted a study in the Kampar River area to assess the status of ecosystem-based fishery resource management across several management models. The research combined qualitative and quantitative methods, using purposive sampling to select 5-10 participants from each village. Following guidelines from the Directorate of Fish Resources, the study developed indicators for each domain and converted them into composite indicators using the 'flag modeling' technique. Data analysis showed that the Lubuk Larangan management model achieved the highest ecosystem-based fishery resource status, scoring 13,374 points (green), indicating optimal implementation of sustainable fisheries management principles. This success necessitates the development of strategic plans to maintain or enhance existing domain conditions and indicators. The individual auction system, communal auction system, and government regulations scored 13,168, 13,120, and 10,899 points respectively (yellow), signifying partial implementation of sustainable fisheries principles.